High-safety ceramic diaphragm with double coatings as well as preparation method and application of high-safety ceramic diaphragm
By adopting a double-layer coating structure in the ceramic separator and using cross-linking curing reaction to form a three-dimensional network structure, the problem of insufficient mechanical strength and temperature resistance of the ceramic separator under high temperature conditions is solved, the liquid absorbency and adhesion to the electrode sheet are improved, and the safety and cycle life of the battery are significantly enhanced.
Patent Information
- Application Number
- CN202411484320.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-10-23
AI Technical Summary
The existing ceramic diaphragms have poor mechanical strength and temperature resistance under high temperature conditions, and are insufficient in liquid absorption, resulting in low safety.
A ceramic separator with a double-layer coating structure is used. Coating A is composed of nanoceramic particles, polyvinyl alcohol and inorganic boron aqueous solution. Coating B is composed of nanoceramic particles and organic boron binder. It forms a three-dimensional network structure through cross-linking and curing reaction, which improves mechanical strength and temperature resistance, and enhances the adhesion to the electrode sheet.
It significantly improves the mechanical strength, temperature resistance and liquid absorption of ceramic diaphragms, and enhances the safety and circulation life of the battery.
Smart Images

Figure BDA0005098329690000081
Abstract
Description
Technical Field
[0001] The invention relates to the field of ceramic diaphragms, and in particular to a high-safety ceramic diaphragm with a double-layer coating, and a preparation method and application thereof. Background Art
[0002] Lithium-ion batteries have become a hot topic in power technology research in recent years due to their advantages of high specific energy, long cycle life, and no memory effect. Lithium-ion batteries play an irreplaceable role in widely used electronic devices such as mobile phones, laptops, etc., as well as the emerging electric vehicles and hybrid vehicles. The main structures of lithium-ion batteries include positive / negative electrode materials, electrolytes, battery separators, and battery shell outer packaging materials. The battery separator is an important component of lithium-ion batteries. It plays a role in directly separating the positive and negative electrodes and preventing battery short circuits. The performance of the battery separator directly determines the interface performance, cycle performance, and safety performance of the battery. Therefore, a separator with excellent performance plays a vital role in improving the comprehensive performance of the battery.
[0003] Ceramics can be dispersed in water and are environmentally friendly. They are currently widely used in the coating of diaphragms to prepare high-temperature resistant ceramic coating diaphragms with good thermal stability. The wettability of the electrolyte is an important indicator for evaluating the diaphragm. Excellent electrolyte wettability is beneficial to improving the ionic conductivity of the battery. In order to further improve the ability of the lithium battery diaphragm to absorb electrolyte, a polymer binder containing polar hydrophilic groups is usually introduced into the diaphragm coating. For example, the patent technical document CN108305972B discloses a ceramic coating diaphragm and a preparation method and application. The ceramic coating diaphragm includes a base film and a ceramic coating, wherein the ceramic coating is coated with inorganic particles with polyethylene glycol grafted on the surface, and the inorganic particles are grafted with polyethylene glycol having a hydroxyl group. Although the ceramic coating diaphragm has a fast liquid absorption rate and a high liquid absorption rate, it exhibits a large thermal shrinkage under high temperature conditions, resulting in poor mechanical strength and temperature resistance of the ceramic coating diaphragm at high temperatures.
[0004] In order to solve the above problems, a cross-linkable polymer binder can be introduced into the diaphragm coating to form a three-dimensional network structure on the diaphragm surface to increase the mechanical strength and temperature resistance of the ceramic coating diaphragm. For example, the patent technical document CN113964450A discloses a battery diaphragm coating liquid and a preparation method thereof, a battery diaphragm and a battery. In the battery diaphragm coating liquid, there are interaction forces or hydrogen bonds between ceramics, adhesives, nanowires and coupling agents, so that the final battery diaphragm has good heat resistance. However, the ceramic diaphragm prepared by this method has a high degree of cross-linking, so that the internal stacking of the system is relatively dense, resulting in a decrease in liquid absorption. In addition, the bonding force between the ceramic diaphragm and the pole piece is poor, and the looseness between the diaphragm and the pole piece may cause an internal short circuit, which in turn causes safety problems such as battery overheating, fire, and even explosion. Summary of the invention
[0005] In view of this, the purpose of the present invention is to propose a high temperature resistance, high liquid absorption ceramic diaphragm and its preparation method and application, which can effectively solve the problems of poor temperature resistance, poor liquid absorption and low safety of the diaphragm, thereby significantly improving the comprehensive performance of the battery.
[0006] Based on the above purpose, the present invention provides a high-safety ceramic diaphragm with a double-layer coating, characterized in that the ceramic diaphragm includes a base membrane and a coating A and a coating B located on both sides of the base membrane; the coating A is obtained by applying a coating A slurry on the surface of the base membrane, and the coating B is obtained by applying a coating B slurry on the surface of the coating A.
[0007] Furthermore, the coating A slurry is prepared from the following raw materials in parts by weight: 70-90 parts of nano-ceramic particles, 4-8 parts of polyvinyl alcohol, 5-10 parts of inorganic boron aqueous solution, 2-3 parts of polyacrylate binder, 0.5-1 part of dispersant, 0.5-1 part of wetting agent and 10-12 parts of deionized water.
[0008] Furthermore, the coating B slurry is prepared from the following raw materials in parts by weight: 70-90 parts of nano-ceramic particles, 4-6 parts of organic boron binder, 0.5-1 part of dispersant, 0.5-1 part of wetting agent and 8-10 parts of deionized water.
[0009] Furthermore, the preparation method of the organic boron binder is as follows:
[0010] S1: Under a nitrogen atmosphere, methyl methacrylate, acrylonitrile, and 3-(methacryloyloxy)propyltrimethoxysilane are added to 1,4-dioxane, and the temperature is raised to 75-80°C, and then benzoyl peroxide and n-dodecyl mercaptan are added, and then the temperature is raised to 90-100°C, and the mixture is stirred for reaction for 2-3 hours, and then washed and purified with petroleum ether to obtain an oligomeric random copolymer;
[0011] S2: In a nitrogen atmosphere, the oligomeric random copolymer and boric acid are mixed, the temperature is raised to 80-90° C., and the mixture is stirred for reaction for 3-4 hours to obtain an organic boron binder;
[0012] Furthermore, the mass ratio of methyl methacrylate, acrylonitrile, 3-(methacryloyloxy)propyltrimethoxysilane, 1,4-dioxane, benzoyl peroxide and n-dodecyl mercaptan in S1 is 10:3:5:50:0.08:1.4.
[0013] Furthermore, the mass ratio of the oligomeric random copolymer to boric acid in S2 is 10:3.
[0014] Furthermore, the base film is one of polyethylene, polypropylene, polymethylpentene and non-woven fabric, and has a porosity of 40-55%.
[0015] Furthermore, the thickness ratio of the base film, coating A and coating B is 10-15:1-4:1-4.
[0016] Furthermore, the nano-ceramic particles are one or more of nano-alumina, aluminum hydroxide, magnesium hydroxide, boehmite and silicon dioxide, and the particle size is 0.4-1.2 μm.
[0017] Furthermore, the concentration of the inorganic boron aqueous solution is 5wt%-10wt%.
[0018] Furthermore, the inorganic boron in the inorganic boron aqueous solution is one or more of borax, potassium tetraborate, lithium tetraborate, and ammonium borate.
[0019] Furthermore, the polyacrylate binder is one of polymethyl acrylate and polybutyl acrylate.
[0020] Furthermore, the dispersant is sodium polyacrylate.
[0021] Furthermore, the wetting agent is one or more of acetylene glycol vinyl ether, fatty acid polyoxyethylene ether and polyether modified siloxane.
[0022] Furthermore, the present invention also provides a method for preparing the above-mentioned high-safety ceramic diaphragm with a double-layer coating, and the specific preparation method is as follows:
[0023] (1) Mix the dispersant and deionized water, stir for 5-10 minutes, add the nano-ceramic particles, stir for 20-90 minutes, grind and disperse for 10-50 minutes, then add the polyacrylate binder, stir for 30-60 minutes, then add polyvinyl alcohol and inorganic boron aqueous solution, stir for 30-60 minutes, then add the wetting agent, stir for 30-60 minutes, and finally filter through a 250-mesh filter to obtain a coating A slurry.
[0024] (2) coating the coating A slurry on the surface of the polyolefin microporous membrane and drying to obtain the coating A;
[0025] (3) Mix the dispersant and deionized water, stir for 5-10 minutes, add the nano-ceramic particles, stir for 20-90 minutes, grind and disperse for 10-50 minutes, then add the organic boron binder, stir for 30-60 minutes, then add the wetting agent, stir for 30-60 minutes, and finally filter through a 250-mesh filter to obtain a coating B slurry;
[0026] (4) The coating B slurry is applied to the surface of the coating A, and after drying, a high-safety ceramic diaphragm with a double-layer coating is obtained.
[0027] Furthermore, the present invention also provides an application of the above-mentioned high-safety ceramic diaphragm with double-layer coating in lithium-ion power batteries.
[0028] Beneficial effects of the present invention:
[0029] The high-safety ceramic diaphragm with a double-layer coating provided by the present invention has a hydroxyl polymer and a boric acid compound in coating A that undergo a cross-linking and curing reaction to form a three-dimensional network structure, thereby improving the coating skeleton strength and effectively improving the mechanical strength and temperature resistance of the diaphragm; the organic boron binder in coating B can better bond the diaphragm to the electrode, while improving the liquid absorption performance of the diaphragm, thereby improving the safety and cycle life of the battery.
[0030] The high-safety ceramic diaphragm with a double-layer coating provided by the present invention, wherein the organic boron binder is an oligomeric random copolymer formed by methyl methacrylate, acrylonitrile, and 3-(methacryloyloxy)propyltrimethoxysilane, which is obtained by modification with boric acid. The organic boron binder has multiple bonding effects, including both the static bonding effect of siloxane and the dynamic bonding effect of organic boric acid, which can effectively improve the bonding force with the electrode and ensure safety. DETAILED DESCRIPTION
[0031] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments.
[0032] Preparation Example: Preparation of organic boron binder:
[0033] S1: Under a nitrogen atmosphere, 10 g of methyl methacrylate, 3 g of acrylonitrile, and 5 g of 3-(methacryloyloxy)propyltrimethoxysilane were added to 50 g of 1,4-dioxane, and the temperature was raised to 75°C. Then, 0.08 g of benzoyl peroxide and 1.4 g of n-dodecyl mercaptan were added, and the temperature was raised to 95°C. The mixture was stirred for reaction for 2.5 h, and then washed and purified with petroleum ether to obtain an oligomeric random copolymer;
[0034] S2: Under a nitrogen atmosphere, 10 g of the oligomeric random copolymer and 3 g of boric acid were mixed, the temperature was raised to 85° C., and the mixture was stirred for reaction for 3.5 h to obtain an organic boron binder.
[0035] Example 1: Preparation of a high-safety ceramic diaphragm with a double-layer coating:
[0036] (1) 0.5 g of sodium polyacrylate and 10 g of deionized water were mixed and stirred for 5 minutes, 70 g of nano-alumina with a particle size of 1 μm was added, stirred for 20 minutes, and then ground and dispersed for 10 minutes. Then 2 g of polymethyl acrylate was added and stirred for 30 minutes. Then 4 g of polyvinyl alcohol and 5 g of a 5 wt% potassium tetraborate aqueous solution were added and stirred for 30 minutes. Then 0.5 g of a wetting agent was added and stirred for 30 minutes. Finally, the mixture was filtered through a 250-mesh filter to obtain a coating A slurry.
[0037] (2) coating the coating A slurry on the surface of a polypropylene microporous membrane with a porosity of 48%, and drying to obtain coating A;
[0038] (3) 0.5 g of sodium polyacrylate and 8 g of deionized water were mixed and stirred for 5 minutes, 70 g of nano-alumina with a particle size of 1 μm was added, stirred for 20 minutes, and then ground and dispersed for 10 minutes. Then 4 g of the organic boron binder prepared in the preparation example was added and stirred for 30 minutes. Then 0.5 g of polyether-modified siloxane was added and stirred for 30 minutes. Finally, the mixture was filtered through a 250-mesh filter to obtain a coating B slurry.
[0039] (4) The coating B slurry is applied to the surface of the coating A, and after drying, a high-safety ceramic diaphragm with a double-layer coating is obtained.
[0040] Example 2: Preparation of a high-safety ceramic diaphragm with a double-layer coating:
[0041] (1) 0.7 g of sodium polyacrylate and 11 g of deionized water were mixed and stirred for 8 minutes, 80 g of nano-alumina with a particle size of 1 μm was added, stirred for 50 minutes, and then ground and dispersed for 30 minutes, then 2.5 g of polymethyl acrylate was added, stirred for 45 minutes, 6 g of polyvinyl alcohol and 8 g of a 7.5 wt% borax aqueous solution were added, stirred for 45 minutes, and 0.8 g of polyether-modified siloxane was added, stirred for 45 minutes, and finally filtered through a 250-mesh filter to obtain a coating A slurry.
[0042] (2) coating the coating A slurry on the surface of a polypropylene microporous membrane with a porosity of 48%, and drying to obtain coating A;
[0043] (3) 0.7 g of sodium polyacrylate and 9 g of deionized water were mixed and stirred for 8 minutes, 80 g of nano-alumina with a particle size of 1 μm was added, stirred for 60 minutes, and then ground and dispersed for 35 minutes, and then 5 g of the organic boron binder prepared in the preparation example was added, stirred for 45 minutes, and then 0.8 g of a wetting agent was added, stirred for 40 minutes, and finally filtered through a 250-mesh filter to obtain a coating B slurry;
[0044] (4) The coating B slurry is applied to the surface of the coating A, and after drying, a high-safety ceramic diaphragm with a double-layer coating is obtained.
[0045] Example 3: Preparation of a high-safety ceramic diaphragm with a double-layer coating:
[0046] (1) 1 g of sodium polyacrylate and 12 g of deionized water were mixed and stirred for 10 minutes, 90 g of nano-alumina with a particle size of 1 μm was added, stirred for 90 minutes, and then ground and dispersed for 50 minutes, and then 3 g of polymethyl acrylate was added and stirred for 60 minutes, and then 8 g of polyvinyl alcohol and 10 g of 10 wt% ammonium borate aqueous solution were added and stirred for 60 minutes, and then 1 g of polyether-modified siloxane was added and stirred for 60 minutes, and finally filtered through a 250-mesh filter to obtain a coating A slurry.
[0047] (2) coating the coating A slurry on the surface of a polypropylene microporous membrane with a porosity of 48%, and drying to obtain coating A;
[0048] (3) 1 g of sodium polyacrylate and 10 g of deionized water were mixed, stirred for 10 minutes, 90 g of nano-alumina with a particle size of 1 μm was added, stirred for 60 minutes, and 1 g of wetting agent was added, stirred for 60 minutes, and finally filtered through a 250-mesh filter to obtain coating B slurry;
[0049] (4) The coating B slurry is applied to the surface of the coating A, and after drying, a high-safety ceramic diaphragm with a double-layer coating is obtained.
[0050] Comparative Example 1:
[0051] Comparative Example 1 is a polypropylene microporous membrane with a porosity of 48%, which is not coated with any coating.
[0052] Comparative Example 2:
[0053] The difference between Comparative Example 2 and Example 2 is that coating B is not provided on Comparative Example 2.
[0054] Comparative Example 3:
[0055] The difference between Comparative Example 3 and Example 2 is that no inorganic boron aqueous solution is added in step (1).
[0056] Comparative Example 4:
[0057] The difference between Comparative Example 4 and Example 2 is that the organic boron binder in step (3) is replaced by polymethyl acrylate.
[0058] Performance Testing
[0059] Referring to GB / T6672-2001 "Mechanical measurement method for the determination of thickness of plastic films and sheets", the thickness of each group of samples in Examples 1-3 and Comparative Examples 1-4 was measured using a THI-1801 thickness gauge in μm;
[0060] Referring to GB / T135I9-2016 standard, the thermal shrinkage rate (%) of each group of samples in Examples 1-3 and Comparative Examples 1-4 placed in an environment of 150° C. for 1 hour was measured using a FST-3102 film thermal shrinkage performance tester;
[0061] Referring to GB / T30447-2013 standard, the contact angle of each group of samples in Examples 1-3 and Comparative Examples 1-4 to the electrolyte was measured using a JC2000D1 contact angle tester;
[0062] The hot pressing bonding strength of the ceramic diaphragms prepared in Examples 1-3 and Comparative Examples 1-4 was tested using a plastic sealing roller press and a universal tensile tester, wherein the roller pressing temperature was set to 113°C, and two ceramic diaphragms were folded in half and aligned at the edges, sandwiched between two PET films, and the temperature of the hot roller was tested with a temperature gun. After reaching the set temperature, the roller press switch was turned on, and the films were placed in parallel in the plastic sealing machine. After all the films left the plastic sealing machine, the PET film was peeled off, and the bonding strength between the ceramic diaphragms was tested using a universal tensile tester peeling method. The results are shown in Table 1 below:
[0063] The adhesion between coating A and coating B was tested by the universal tensile machine peeling method. The results are shown in Table 1.
[0064] Table 1 Performance test results
[0065]
[0066] Data Analysis:
[0067] It can be seen from Table 1 that, relative to the base film in Comparative Example 1, the high-safety ceramic diaphragm with a double-layer coating prepared in Examples 1-3 has a lower thermal shrinkage rate, a higher air permeability value and a smaller contact angle at both 150°C and 180°C, and has a certain hot pressing bonding force to ensure safety.
[0068] It can be seen from the data of Example 2 and Comparative Example 2 that coating B effectively reduces the thermal shrinkage of the diaphragm at 150°C and 180°C, improves the heat resistance, and further improves the contact angle. Most importantly, it imparts a certain hot pressing bonding force to the diaphragm.
[0069] It can be seen from the data of Example 2 and Comparative Example 3 that the addition of inorganic boron significantly improves the heat resistance of the separator and, most importantly, improves the bonding force between coating A and coating B.
[0070] It can be seen from the data of Example 2 and Comparative Example 4 that, compared with the traditional polyacrylate adhesive, the organic boron adhesive prepared by the present invention significantly improves the heat resistance of the separator and makes an outstanding contribution to the hot pressing adhesive force.
[0071] Those skilled in the art should understand that the discussion of any of the above embodiments is merely illustrative and is not intended to imply that the scope of the present invention is limited to these examples. Under the concept of the present invention, the technical features in the above embodiments or different embodiments may be combined, the steps may be implemented in any order, and there are many other variations of the different aspects of the present invention as described above, which are not provided in detail for the sake of simplicity.
Claims
1. A high-safety ceramic diaphragm with a double-layer coating, characterized in that: The ceramic diaphragm comprises a base membrane and a coating A and a coating B located on both sides of the base membrane; the coating A is obtained by coating the coating A slurry on the surface of the base membrane, and the coating B is obtained by coating the coating B slurry on the surface of the coating A; The coating A slurry is prepared from the following raw materials in parts by weight: 70-90 parts of nano-ceramic particles, 4-8 parts of polyvinyl alcohol, 5-10 parts of inorganic boron aqueous solution, 2-3 parts of polyacrylate binder, 0.5-1 part of dispersant, 0.5-1 part of wetting agent and 10-12 parts of deionized water; The coating B slurry is prepared from the following raw materials in parts by weight: 70-90 parts of nano-ceramic particles, 4-6 parts of organic boron binder, 0.5-1 part of dispersant, 0.5-1 part of wetting agent and 8-10 parts of deionized water; The preparation method of the organic boron binder is as follows: S1: Under a nitrogen atmosphere, methyl methacrylate, acrylonitrile, and 3-(methacryloyloxy)propyltrimethoxysilane are added to 1,4-dioxane, and the temperature is raised to 75-80°C, and then benzoyl peroxide and n-dodecyl mercaptan are added, and then the temperature is raised to 90-100°C, and the mixture is stirred for reaction for 2-3 hours, and then washed and purified with petroleum ether to obtain an oligomeric random copolymer; S2: In a nitrogen atmosphere, the oligomeric random copolymer and boric acid are mixed, the temperature is raised to 80-90° C., and the mixture is stirred for reaction for 3-4 hours to obtain an organic boron binder; The mass ratio of methyl methacrylate, acrylonitrile, 3-(methacryloyloxy)propyltrimethoxysilane, 1,4-dioxane, benzoyl peroxide and n-dodecyl mercaptan in S1 is 10:3:5:50:0.08:1.4; the mass ratio of the oligomeric random copolymer and boric acid in S2 is 10:
3.
2. The high-safety ceramic diaphragm with double-layer coating according to claim 1, characterized in that: The base film is one of polyethylene, polypropylene, polymethylpentene and non-woven fabric, and has a porosity of 40-55%.
3. The high-safety ceramic diaphragm with double-layer coating according to claim 1, characterized in that: The thickness ratio of the base film, coating A and coating B is 10-15:1-4:1-4.
4. The high-safety ceramic diaphragm with double-layer coating according to claim 1, characterized in that: The nano ceramic particles are one or more of nano alumina, aluminum hydroxide, magnesium hydroxide, boehmite and silicon dioxide, and the particle size is 0.4-1.2 μm.
5. The high-safety ceramic diaphragm with double-layer coating according to claim 1, characterized in that: The concentration of the inorganic boron aqueous solution is 5wt%-10wt%.
6. The high-safety ceramic diaphragm with double-layer coating according to claim 1, characterized in that: The inorganic boron in the inorganic boron aqueous solution is one or more of borax, potassium tetraborate, lithium tetraborate and ammonium borate.
7. The high-safety ceramic diaphragm with double-layer coating according to claim 1, characterized in that: The polyacrylate binder is one of polymethyl acrylate and polybutyl acrylate.
8. The high-safety ceramic diaphragm with double-layer coating according to claim 1, characterized in that: The dispersant is sodium polyacrylate; the wetting agent is one or more of acetylene glycol vinyl ether, fatty acid polyoxyethylene ether and polyether modified siloxane.
9. A method for preparing a high-safety ceramic diaphragm with a double-layer coating according to any one of claims 1 to 8, characterized in that: The specific preparation method is as follows: (1) Mix the dispersant and deionized water, stir for 5-10 minutes, add the nano-ceramic particles, stir for 20-90 minutes, grind and disperse for 10-50 minutes, then add the polyacrylate binder, stir for 30-60 minutes, then add polyvinyl alcohol and inorganic boron aqueous solution, stir for 30-60 minutes, then add the wetting agent, stir for 30-60 minutes, and finally filter through a 250-mesh filter to obtain a coating A slurry. (2) coating the coating A slurry on the surface of the polyolefin microporous membrane and drying to obtain the coating A; (3) Mix the dispersant and deionized water, stir for 5-10 minutes, add the nano-ceramic particles, stir for 20-90 minutes, grind and disperse for 10-50 minutes, then add the organic boron binder, stir for 30-60 minutes, then add the wetting agent, stir for 30-60 minutes, and finally filter through a 250-mesh filter to obtain a coating B slurry; (4) The coating B slurry is applied to the surface of the coating A, and after drying, a high-safety ceramic diaphragm with a double-layer coating is obtained.
10. An application of a high-safety ceramic diaphragm with a double-layer coating according to any one of claims 1 to 8, characterized in that: Can be applied to lithium-ion power batteries.
Citation Information
Patent Citations
A ceramic-coated diaphragm, its preparation method, and its application.
CN108305972B
Battery diaphragm coating liquid and preparation method thereof, battery diaphragm and battery
CN113964450A
Boron-containing ceramic separator as well as preparation method and application thereof
CN104466062A
Organic and inorganic composite modified diaphragm and preparation method and application thereof
CN106887556A
Ceramic diaphragm based on organic-inorganic composite binder and preparation method thereof
CN113937419A